Hostility: Its impact on health and psychometric measuring in Latin America - Moscoso, Manolete S. (2008)
The article describes the importance of research on hostility and its consequences on health and the connections between emotions and immune system. We present a view of the conceptual and theoretical framework of hostility. One of the main goals of this study was to report the construct validity of the Multicultural Latin American Hostility Inventory. Responses to the items, were factored in separate principal factor analysis with promax rotations to determine the level of correspondence of factor structure in the instrument. This inventory presents with empirical evidence that demonstrates a high degree of construct validity and internal consistency as shown by its factorial structure and alpha correlations.